The change of long tail fibers expanded the host range of a T5-like Salmonella phage and its application in milk - Xiaofeng Zheng; Xin Wang; Pei Li; Yu Zhou; Xihui Zhu; Zimeng Hu; Hui Wang; Mianmian Chen; Xiang Huo; Yingyu Liu; Wei Zhang (BMC Microbiology)
Abstract We engineered novel T5-like bacteriophage (phage) with extended host ranges by editing the long-tail fibers (PB3 and PB4) to combat Salmonella Enteritidis. By replacing the long-tail fibers PB3 and PB4 regions of phage PH204 with those from phage SP76, we created phages RPA1 − 3 and RPB1 − 3, which exhibited expanded host ranges, lysing 54 strains compared to the original 30 strains. These phages retained the biological characteristics of PH204, including temperature, pH stability and adsorption rate. In milk, RPA1 − 3 and RPB1 − 3 inhibited Salmonella ZWSA605 growth, reducing bacterial counts to 1.51 log10 CFU/mL and 2.18 log10 CFU/mL after 8 h, respectively. Although the bacteriolytic activity of recombinant phages is lower than that of the parent phage, our findings suggest that these phages hold promise as candidates for future phage biocontrol applications in food.